2018
DOI: 10.1111/wrr.12620
|View full text |Cite
|
Sign up to set email alerts
|

Nerve reinnervation and itch behavior in a rat burn wound model

Abstract: In this study, we investigated whether postburn itch in rats, after a full thickness burn, is correlated to the nervous reinnervation of the burn wound area. For this purpose, we determined scratching duration (expressed as second/hour) at 24 hours, 2, 4, 8, and 12 weeks postburn and combined this with immunohistochemistry for protein gene product 9.5 (PGP9.5) to identify all nerve fibers, calcitonin gene related peptide (CGRP) to identify peptidergic fibers, tyrosine hydroxylase (TH) for sympathetic fibers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…In their rat model, PGP 9.5-and CGRP-immunoreactive nerve fibers reappeared four weeks after the burn injury, while H-and GAP-43-IR nerve fibers remained absent. Peptidergic and non/peptidergic nerve fibers, except sympathetic noradrenergic nerve fibers, could be verified in the developed scar tissue 2 weeks after a full-thickness injury and returned to normal 8-12 weeks after burn trauma in the center of the lesion [21].…”
Section: Animal Experimentsmentioning
confidence: 83%
See 1 more Smart Citation
“…In their rat model, PGP 9.5-and CGRP-immunoreactive nerve fibers reappeared four weeks after the burn injury, while H-and GAP-43-IR nerve fibers remained absent. Peptidergic and non/peptidergic nerve fibers, except sympathetic noradrenergic nerve fibers, could be verified in the developed scar tissue 2 weeks after a full-thickness injury and returned to normal 8-12 weeks after burn trauma in the center of the lesion [21].…”
Section: Animal Experimentsmentioning
confidence: 83%
“…Splitting perception into single sensory qualities, the animal studies revealed that 8 weeks after full-thickness burn injury, nociceptive function is renewed, mainly in distant sites and reduced in the wound center and at the edges [20]. Saffari et al [21] reported that 24 h after thermal insult, nerve fibers were completely absent in the wound. In their rat model, PGP 9.5-and CGRP-immunoreactive nerve fibers reappeared four weeks after the burn injury, while H-and GAP-43-IR nerve fibers remained absent.…”
Section: Animal Experimentsmentioning
confidence: 99%